NOVEL RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR ESTIMATION OF TELMISARTAN AND NEBIVOLOL HCL IN PHARMACEUTICAL DOSAGE FORM - Shaikh, Heena Ar; Jain, Vandana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A simple, accurate, precise, robust reverse phase high performance liquid chromatography (RP-HPLC) method was developed for the estimation of telmisartan and nebivolol hydrochloride (HCl) simultaneously in its combined dosage form. Methods: The compounds were well resolved in an isocratic method using the mobile phase composition of acetonitrile: Buffer (potassium dihydrogen orthophosphate pH adjusted 3.1 with orthophosphoric acid) in a ratio of 40:60 v/v at a flow rate of 1.2 ml/min using C18 Shim-pack (150 mm × 4.6 mm, 5 μ) column. The detection was carried out at 280 nm. Results: The retention time of telmisartan and nebivolol HCl was 4.8 min and 6.5 min, respectively. The developed method was validated by evaluating various validation parameters such as linearity, precision, accuracy, robustness, specificity, limit of detection, and limit of quantification according to the international council for harmonization guidelines. The standard calibration curve was obtained in the concentration range of 24–56 μg/ml for telmisartan and 3–7 μg/ml for nebivolol HCl. The overall average % recovery was found out to be 100.35 for telmisartan and 98.84 for nebivolol HCl. Conclusion: Statistical analysis of the data showed that the method is reproducible and selective for the estimation of telmisartan and nebivolol HCl. The proposed method could be used for analysis of telmisartan and nebivolol HCl in their dosage form.